Newton a tale of two Isaacs - Nest Entertainment, Inc. (Toronto, Ont. : Devine Entertainment, 2002)
A dramatization of the life of Sir Isaac Newton as told by a young boy named after him. Thus the tale of the two Isaacs is interwoven throughout the story.
Originally broadcast in 1997 as an HBO original production.
Karl Pruner, Tyrone Savage, Kris Lemche, Lisa Jakub, Adrian Hough, Nigel Bennett, Catherine Byrne, Richard McMillan, Leif Bristow.
DVD ; Dolby digital stereo.
In English, Spanish and French.
Closed-captioned.
Keywords: Newton, Isaac, -- 1642-1727 -- Juvenile drama; Physicists -- Biography -- Drama; Scientists -- Drama; Children's films; Video recordings for hard of hearing people